About different uses of nothingness: mystical and philosophical-political - Becker-Lorca, Martin Stephan (Resonancias. Revista de Filosofía, 2024)
This article describes three uses of the concept of nothingness. First, in the field of Christian mysticism, I analyze the treatment of this category by the 13th century Dominican monk Meister Eckhart; then, within the philosophical-political sphere, I study the uses of this notion by the Argentine liberation philosopher Enrique Dussel and the North American poet and cultural theorist Fred Moten. My intention is to investigate possible influences of Christian mysticism’s use of nothingness on the philosophical-political field. I argue that in all three cases there is a dynamic of nothingness that ends with an inversion, in which one passes from the experience of nothingness as a defect or deprivation to nothingness as excess, that is, from the sub-ontological to the trans-ontological. I demonstrate that these three uses of nothing are based on the revenue that this inversion makes possible.